PENYULUHAN APLIKASI 3 DIMENSI BERBASIS MODELING DAN RENDERING UNTUK PENDIDIKAN YANG KREATIF PADA SEKOLAH DASAR ISLAM AL-CHASANAH - Gamal S., Geggy (Universitas Esa Unggul, 2017)
AbstractThe Faculty of Design & Creative Industry (FDCI) Esa Unggul University who joined with the Faculty of Computer Science (FacComSci) interested to developing the talents of teachers at Al-Chasanah Islamic Primary School with the intention of advancing creative human resources by transferring knowledge to teachers and staff education in order to understand and be capable of learning development as needed. This scholarship aims at the field of application of computer-based information systems as a supporter of education services. Educational services on a computer basis are aspects that must be absorbed by Indonesian educators, especially primary school teachers. One of the scholarships that will be presented and shared to these teachers is the field of graphic design related to the manufacture of 3-dimensional model and the rendering process. The implementation method uses 3 types of phases, the first phase is a presentation using a projector as a media. The second phase is a Q/A process and a discussion of 3 dimensional knowledge. And the third phase is the tutorial and training phase where teachers practicing directly using the schools computer lab. The importance of this dedication to the community is to have a basic 3-dimensional design knowledge that is still minimal knowledge of these sciences in the teachers of the nations children. With the counseling with this science, the teachers already have the basic science of 3-dimensional modeling and 3 dimensional rendering in order to be a multitasking human resources, especially in the knowledge of design based on creative industry where this knowledge will become a benchmark for the creativity that become interconnected with creative economy.Â Keywords : 3 dimensional graphic, 3 dimensional design, modeling and renderingÂ AbstrakFakultas Desain & Industri Kreatif (FDIK) Universitas Esa Unggul yang bergabung dengan Fakultas Ilmu Komputer (Fasilkom) tertarik dalam mengembangkan bakat guru-guru pada Sekolah Dasar Islam Al-Chasanah dengan maksud memajukan sumber daya manusia yang kreatif dengan cara transfer knowledge kepada guru dan staf pendidikan agar memahami dan berkemampuan untuk pengembangan pembelajaran sesuai kebutuhan. Keilmuan ini bertujuan dalam bidang penerapan sistem informasi berbasis komputer sebagai pendukung pelayanan pendidikan. Pelayanan pendidikan dengan basis komputer merupakan aspek yang harus sudah diserap oleh pendidik-pendidik Indonesia terutama guru-guru SD. Salah satu keilmuan yang akan dipaparkan dan dibagi kepada guru-guru tersebut adalah bidang desain grafis yang berkaitan dalam pembuatan model 3 dimensi dan proses renderingnya. Metode pelaksanaannya menggunakan 3 jenis fase, fase pertama adalah presentasi dengan menggunakan proyektor sebagai media nyuluh. Fase kedua adalah proses tanya jawab dan diskusi tentang pengetahuan 3 dimensi. Dan fase ketiga adalah fase tutorial dan training dimana para guru mempraktekkannya secara langsung dengan menggunakan komputer lab milik sekolah. Pentingnya pengabdian ini kepada masyarakat adalah memiliki dasar ilmu desain 3 dimensi yang masih minim pengetahuan akan ilmu-ilmu ini di para pengajar anak-anak bangsa. Dengan adanya penyuluhan dengan ilmu ini, para guru sudah memiliki dasar ilmu desain 3 dimensi modeling dan 3 dimensi rendering guna akan menjadi sumber daya manusia yang multitasking terutama pada ilmu desain industri kreatif dimana ilmu tersebut akan menjadi tolak ukur dalam berkreativitas yang saling berkaitan dengan ekonomi kreatif.Â Kata Kunci : grafis 3 dimensi, desain 3 dimensi, modeling dan rendering